1988
DOI: 10.1021/j100328a009
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and structure of water bound to DNA

Abstract: The dynamical properties of DNA (from Escherichia coli and salmon testes) in SSC buffer were investigated by the use of the time domain reflectometry method; accurate measurements on the complex permittivity were carried out. A relaxation process due to bound water was discovered around 100 MHz in addition to the relaxation process due to free water observed around 20 GHz. The former shows a dielectric transition of the order-disorder type at the denaturation temperature Tm. Invariant temperature dependence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 1 publication
1
18
0
Order By: Relevance
“…They show up peaks between 50 and 80 MHz, 0.9 and 1.2 GHz and 15 and 18 GHz for the b-, d-and g-relaxations, respectively, which slightly shi towards lower frequencies with decreasing temperature. Similar kinds of peaks have been observed previously for rigid biopolymers such as DNA and collagen, which show a dielectric relaxation peak around 100 MHz independently of bulk water relaxation observed around 20 GHz, [56][57][58] and it was concluded that the observed peak was due to the orientation of water molecules bound to these polymers.…”
Section: Resultssupporting
confidence: 85%
“…They show up peaks between 50 and 80 MHz, 0.9 and 1.2 GHz and 15 and 18 GHz for the b-, d-and g-relaxations, respectively, which slightly shi towards lower frequencies with decreasing temperature. Similar kinds of peaks have been observed previously for rigid biopolymers such as DNA and collagen, which show a dielectric relaxation peak around 100 MHz independently of bulk water relaxation observed around 20 GHz, [56][57][58] and it was concluded that the observed peak was due to the orientation of water molecules bound to these polymers.…”
Section: Resultssupporting
confidence: 85%
“…Recently we used the time‐domain reflectometry (TDR) to disclose dynamic features of this system, particularly the characteristic structures and properties of water 19, 20. This is because TDR is a method developed by Cole and Mashimo21–25 for measuring dielectric dispersion in the 1 MHz to 10 GHz and used effectively for aqueous biopolymer solutions 25–34. So far heat capacity measurements have been made on H 2 O and D 2 O solutions of relatively low concentrations (below 21.1 wt %)9, 10, 13, 19 and TDR measurements on 14.7, 17.8, and 20 wt % solutions 19, 20.…”
Section: Introductionmentioning
confidence: 99%
“…Recently we have found the dielectric relaxation peak due to the bound water around 100 MHz. 11,12 The measurements were performed a t temperatures higher than 0°C and in dilute aqueous solutions with appropriate buffer. The results obtained offer what information is available on hydration of DNA in vivo.…”
Section: Introductionmentioning
confidence: 99%